2017
DOI: 10.1371/journal.pone.0172495
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific leaf trait variability along a boreal-to-tropical community diversity gradient

Abstract: Disentangling the mechanisms that shape community assembly across diversity gradients is a central matter in ecology. While many studies have explored community assembly through species average trait values, there is a growing understanding that intraspecific trait variation (ITV) can also play a critical role in species coexistence. Classic biodiversity theory hypothesizes that higher diversity at species-rich sites can arise from narrower niches relative to species-poor sites, which would be reflected in red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…However, a recent study across a large latitudinal gradient did not find greater individual variation with higher species diversity (Bastias et al . ). Second, we found that higher phenotypic variability in non‐preferred habitats can only foster coexistence if the variance of the inferior competitor is high relative to that of the superior competitor, enabling the inferior competitor to persist.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, a recent study across a large latitudinal gradient did not find greater individual variation with higher species diversity (Bastias et al . ). Second, we found that higher phenotypic variability in non‐preferred habitats can only foster coexistence if the variance of the inferior competitor is high relative to that of the superior competitor, enabling the inferior competitor to persist.…”
Section: Discussionmentioning
confidence: 97%
“…), most empirical studies of species coexistence have ignored the role of individual variation (but see Clark ; Siefert ; Bastias et al . ). Ignoring IV is justifiable if it has no influence on coexistence, but problematic if IV affects coexistence.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, at higher PPFD the photosynthetic ( A max and WUE i ) and photochemical (ΦPSII, ETR and qP) responses were significantly higher in HL‐acclimated plants, suggesting that G. avellana can behave as a light‐demanding species which is flexible enough to grow under LL. There is a growing understanding of late that high intraspecific variability in leaf traits plays a critical role in the ecological breadth and competitive ability of species (Clark, ; Valladares et al ., ; Bastias et al ., ). This is further supported by our observations on morphological and physiological variation along light gradients in G. avellana (Ostria‐Gallardo et al ., , and the present study).…”
Section: Discussionmentioning
confidence: 97%
“…This may also explain the conflicting results obtained in recent studies. While some studies support equalizing mechanisms as drivers of community assembly (more trait overlap in species‐rich communities, for example, Le Bagousse‐Pinguet et al, ; Li et al, ), others better support niche theory (less trait overlap in species‐rich communities, for example, Siefert et al, ; Kumordzi et al, ) or neutral theory (no change, Bastias et al, ). These studies are, however, all focused on plant communities, communities that are typically richer than the ones presented here (3‐12 species per pond; e.g., Bastias et al, ).…”
Section: Discussionmentioning
confidence: 99%